Functional modulation of atrio-ventricular conduction by enhanced late sodium current and calcium-dependent mechanisms in Scn5a1798insD/+ mice. Issue 10 (10th August 2020) - Rivaud, Mathilde R; Marchal, Gerard A; Wolswinkel, Rianne; Jansen, John A; van der Made, Ingeborg; Beekman, Leander; Ruiz-Villalba, Adrián; Baartscheer, Antonius; Rajamani, Sridharan; Belardinelli, Luiz; van Veen, Toon A B; Basso, Cristina; et al.
Abstract: Aims: SCN5A mutations are associated with arrhythmia syndromes, including Brugada syndrome, long QT syndrome type 3 (LQT3), and cardiac conduction disease. Long QT syndrome type 3 patients display atrio-ventricular (AV) conduction slowing which may contribute to arrhythmogenesis. We here investigated the as yet unknown underlying mechanisms. Methods and results: We assessed electrophysiological and molecular alterations underlying AV-conduction abnormalities in mice carrying the Scn5a 1798insD/+ mutation. Langendorff-perfused Scn5a 1798insD/+ hearts showed prolonged AV-conduction compared to wild type (WT) without changes in atrial and His-ventricular (HV) conduction. The late sodium current ( I Na, L ) inhibitor ranolazine (RAN) normalized AV-conduction in Scn5a 1798insD/+ mice, likely by preventing the mutation-induced increase in intracellular sodium ([Na + ]i ) and calcium ([Ca 2+ ]i ) concentrations. Indeed, further enhancement of [Na + ]i and [Ca 2+ ]i by the Na + /K + -ATPase inhibitor ouabain caused excessive increase in AV-conduction time in Scn5a 1798insD/+ hearts. Scn5a 1798insD/+ mice from the 129P2 strain displayed more severe AV-conduction abnormalities than FVB/N- Scn5a 1798insD/+ mice, in line with their larger mutation-induced I Na, L . Transverse aortic constriction (TAC) caused excessive prolongation of AV-conduction in FVB/N- Scn5a 1798insD/+ mice (while HV-intervals remained unchanged), which was prevented by chronic RAN treatment. Scn5a 1798insD/+ -TAC hearts showed decreased mRNA levels of conduction genes in the AV-nodal region, but no structural changes in the AV-node or His bundle. In Scn5a 1798insD/+ -TAC mice deficient for the transcription factor Nfatc2 (effector of the calcium-calcineurin pathway), AV-conduction and conduction gene expression were restored to WT levels. Conclusions: Our findings indicate a detrimental role for enhanced I Na, L and consequent calcium dysregulation on AV-conduction in Scn5a 1798insD/+ mice, providing evidence for a functional mechanism underlying AV-conduction disturbances secondary to gain-of-function SCN5A mutations.